INTERFERENSI BAHASA LAIN KE DALAM BAHASA INDONESIA PADA RUBRIK OPINI KORAN JAWA POS EDISI BULAN JULI TAHUN 2012 - Yatiningsih Yatiningsih (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2014)
The purpose of this study is as follows: (1) To describe the interference lexicon Java language, English and Arabic into Indonesian in newspaper opinion column Jawa Pos newspaper edition in July of 2012. (2) Interference phrases to describe the Java language, English and Arabic into Indonesian on the rubric Opinion newspaper Jawa Pos newspaper edition in July of 2012. (3) To describe the interference clause Java language, English and Arabic into Indonesian on the rubric Opinion newspaper Jawa Pos newspaper edition in July of 2012. (4) To describe what factors underlying the variety of languages used in the Opinion section newspaper Jawa Pos newspaper edition in July of 2012.This study is a qualitative research. The analysis technique used in this study is a technique developed Miles, the interactive model. Interactive model consists of three stages. The third stage includes: data reduction, data presentation, and withdrawal kesimmpulan. Based on the data analysis conducted by researchers, it can be concluded the following:(1) Interference lexicon Java language, English, Arabic into Indonesian language used by the author Opinion newspaper Jawa Pos, a number of data sources are listed in table 48. The use of these words should not be used to in Indonesian as an interference events and the existing Indonesian correct form. (2) Interference phrases Java language, English and Arabic into Indonesian look at the research table, (3) Interference clause Java language, English and Arabic into Indonesian can be seen in the table of 48 studies that included data sources. (4) the factors underlying the use of language diversity in the Opinion section: Setting or background regarding the time and place in the Opinion section Jawa Pos newspaper, partisipans that speakers and writers as well as readers and community.